Qualitative platelet defect and thrombohaemorrhagic complications in a patient with polycythaemia vera - Friess, D.; Lämmle, B.; Alberio, L. (Hämostaseologie, 2003)
We describe a 67-year-old patient with polycythaemia vera and pathological functional platelet studies. He not only suffered a transient ischaemic attack despite taking of antiplatelet agents, but also showed bleeding diathesis with cerebral bleeding and spontaneous suffusions. Platelet function studies and clinical findings improved after phlebotomy and cytoreductive treatment with hydroxyurea.Thrombosis and haemorrhage account predominantly for morbidity and mortality in patients with polycythaemia vera. The pathophysiological mechanisms to explain thrombosis and bleeding in patients with myeloproliferative disorders including polycythaemia vera were intensively studied. However, up to now no clear correlation of laboratory findings in relation to clinical history of thrombosis and bleeding was demonstrated. In this report the most important pathophysiological mechanisms and therapy with antiplatelet agents are discussed.
Keywords: Polycythaemia vera; platelet function; thrombosis; antiplatelet agents